Off/Scene Representation: on the Construction of Sexuality in Pornographic Cinema - Kratje, Julia (2013)
Various manifestations of pornography have been emphatically addressed by feminist studies and critique. In that context, the pornographic movie genre and erotic cinema are often considered part of a phallogocentric universe of meaning. Some dissonant views exist, however, relative to the conception of pornography as a clear reproducer of women’s sexual oppression. Bearing in mind the aforementioned debates, this work analyzes the representational dimension of pornographic films from a socio-cultural standpoint, focusing on the rhetoric of pornography and on its effects on the construction of the contemporary socio-sexual universe.